Effects of Feeding Frequency on Turbot (Scophthalmusmaximus) Performance, Water Quality and Microbial Community in Recirculating Aquaculture Systems - Xiaoyang Guo; Jiyuan Li; Shihong Xu; Xin Jiang; Teng Guo; Feng Liu; Guang Gao; Jun Li; Yanfeng Wang; Wei Jiang (Fishes, 2025)
Recirculating aquaculture systems (RAS) have promising applications in aquaculture. Feed is recognized as a major source of input to the RAS, and feeding frequency will not only impact the performance of turbot, but will also impact the quality of the cultured water. In order to rationally manage feeding and reduce aquaculture pollution, this study investigated the effects of feeding frequency on the performance of turbot (Scophthalmus maximus), nitrogen removal (ammonia and nitrite) characteristics and microbial communities in biofilters. The experiment was designed with three treatment groups, which were categorized into feeding once/day (FF1), feeding twice/day (FF2) and feeding three times/day (FF3) for 30 days. The results indicated that weight gain rate (WGR) and specific growth rate (SGR) significantly increased (p < 0.05) in the FF2 group and FF3 group compared with the FF1 group. The feed conversion ratio (FCR) was significantly lower (p < 0.05) in the FF2 group and FF3 group than in the FF1 group. There was no significant change in condition factor (CF). Ammonia and nitrite concentration decreased and water quality fluctuated less as the feeding frequency increased. FF2 showed the highest ammonia and nitrite removal rates. Feeding frequency did not significantly affect biofilter alpha diversity, but significantly altered beta diversity. PICRUSt functional prediction analysis revealed that the relative abundance of functional genes for nitrogen metabolism (amoA, amoB, amoC, hao, nxrA and nxrB) was highest in FF2. Therefore, feeding frequency of twice/day not only benefits the performance of turbot but also stabilizes the water environment and improves the removal of ammonia nitrogen and nitrite in RAS. These results provide theoretical and practical basis for further water improvement by seawater RAS.